FRI0393 PATIENTS' SATISFACTION AND PREFERENCES TOWARDS SUPERVISED GROUP EXERCISE FOR PEOPLE WITH AXIAL SPONDYLOARTHRITIS. (June 2019) - Hilberdink, Bas; Giesen, Florus van der; Vlieland, Thea Vliet; van Gaalen, Floris A.; Weely, Salima van
Abstract : Background: Supervised group exercise (SGE) is proven effective in patients with axial spondyloarthritis (axSpA), but its contents and dosage do not always comply with current scientific insights. 1 In particular vigorous intensity cardiorespiratory exercise is considered to be an important element of exercise programs in axSpA. 2 For successful implementation of any adjustments, axSpA patients' satisfaction and preferences towards SGE needs to be determined. Objectives: This study aimed to describe axSpA patients' satisfaction with current SGE and perspective on potential, evidence-based SGE enhancements. Methods: AxSpA patients participating in SGE in four regions in the Netherlands (n=118) completed a survey on their satisfaction with features of current SGE (eight questions, 3-point Likert scale, and one overall grade, 11-point scale) and their perspective on introducing appropriately dosed cardiorespiratory and strengthening exercise, monitoring exercise intensity, periodic (re)assessments, patient education and supervision by physical therapists with specific expertise (four dichotomous questions and one 5-point Likert scale). In addition, sociodemographic and disease characteristics were recorded. Results: The patients' mean age was 60 years (SD ±12), 64% was male and they participated in SGE for 25 years (SD ±14) on average. The SGE programs in the four regions all took place once weekly between 90 to 135 minutes and all consisted of mobility exercises, sports activities and hydrotherapy. Two regions also focused on strengthening and only one specifically addressed cardiorespiratory exercise. Most patients were satisfied with the current total intensity (n=84/112, 75%), duration (n=93/111, 84%) and load (n=89/117, 76%) of the program and the proportion of mobility (n=102/114, 90%), strengthening (n=90/115, 78%) and cardiorespiratory exercise (n=82/114, 72%). The median overall grade of the program was a 7 (IQR=7-8). Most patients agreed with the implementation of more frequent (home) exercise (n=73/117, 62%), heartrate monitoring (n=97/117, 83%) and periodic (re)assessments (n=97/118, 82%), whereas 50% agreed with the addition of structured patient education (n=37/74). The majority found supervision by therapists specialized in axSpA highly important (n=105/118, 89%). Conclusion: The majority of axSpA-specific SGE participants was satisfied with current SGE, but also agreed with enhancements in line with scientific evidence. The high satisfaction levels with the amount of cardiorespiratory exercise, despite only being targeted in one SGE region, suggests a knowledge gap regarding its (health) benefits. Current satisfaction levels indicate that a planned implementation strategy, including education and addressing potential barriers and facilitators for the uptake of enhancements, is warranted. References: [1] Dagfinrud, et al. Arthritis Care Res. 2011;63(4):597-603. [2] Niedermann, et al. Arthritis Care Res. 2018. Doi:10.1002/acr.23705 Acknowledgement: The authors thank the Dutch Arthritis Society for funding this study and for thinking along from the patients' perspective. They also thank all participants, coordinators, boards and guiding therapists from the four included SGE regions. Disclosure of Interests: None declared